2014
DOI: 10.1364/ao.54.000a84
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional information encryption and anticounterfeiting using digital holography

Abstract: In this work, arbitrary micro phase-step digital holography with optical interferometry and digital image processing is utilized to obtain information about an image of a three-dimensional object and encrypting keys. Then, a computer-generated hologram is used for the purpose of holographic encryption. All information about the keys is required to perform the decryption, comprising the amplitude and phase distribution of the encrypting key, the distance of image reconstruction, zero-order term elimination, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…[13] Meanwhile, Kim et al demonstrated a technique for 3D information security with virtual optics based hologram encryption. [14] Kong et al proposed a novel approach for encrypting 3D scene information hierarchically based on computer-generated holograms (CGHs). [15] However, the above mentioned encryption systems are encrypting on a single object.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Meanwhile, Kim et al demonstrated a technique for 3D information security with virtual optics based hologram encryption. [14] Kong et al proposed a novel approach for encrypting 3D scene information hierarchically based on computer-generated holograms (CGHs). [15] However, the above mentioned encryption systems are encrypting on a single object.…”
Section: Introductionmentioning
confidence: 99%
“…These disadvantages prevent information on 3D objects from being stored or transported efficiently and conveniently in practice. Thus, most holography-based hiding systems are realized by computer simulation [19][20][21][22]. Recently, some new holographic techniques for 3D object hiding have emerged with partial experimental realization.…”
Section: Introductionmentioning
confidence: 99%
“…Counterfeiting, prevalent in banknotes, confidential documents, brands, pharmaceuticals, and jewelry, has become a serious worldwide problem because it causes harmful impacts on global economy, security, and health. , Therefore, it is highly desirable to develop more reliable anticounterfeiting techniques with improved security levels, easy identification, and difficulty of duplication. In the past several decades, various kinds of anticounterfeiting techniques have been developed to combat counterfeiting and information leakage, such as plasmonic security labels, watermarks, holograms, magnetic response, and fluorescent anticounterfeiting. Among them, fluorescent anticounterfeiting technology based on fluorescent materials particularly attracts much attention and has been widely used in the fields of data storage and information security due to its remarkable properties of high throughput, flexible design, low cost, and facile operation. However, conventional fluorescent materials only provide static optical outputs, which are easily duplicated by certain substitutes with similar emission characteristics, resulting in poor anticounterfeiting performance. In contrast, fluorescent materials with stimuli-responsive ability, which can alter their optical outputs of spectra and lifetime in response to external stimuli, have drawn considerable attention in security protection field. In recent years, a variety of stimuli-responsive fluorescent materials, including transition-metal complexes, organic dyes, , lanthanide-doped upconversion nanoparticles, inorganic quantum dots, ,, polymers dots, , metal–organic frameworks, and perovskites have been investigated. Upon exposure to specific external stimuli, these materials were capable of changing optical outputs through controlling the energy transfer paths, , regulating the microstructures, ,, or adjusting their chemical constitutions, which provided extra security features and improved security levels for anticounterfeiting efforts.…”
mentioning
confidence: 99%
“…1,2 Therefore, it is highly desirable to develop more reliable anticounterfeiting techniques with improved security levels, easy identification, and difficulty of duplication. In the past several decades, various kinds of anticounterfeiting techniques have been developed to combat counterfeiting and information leakage, such as plasmonic security labels, 3 watermarks, 4 holograms, 5 magnetic response, and fluorescent anticounterfeiting. 6−10 Among them, fluorescent anticounterfeiting technology based on fluorescent materials particularly attracts much attention and has been widely used in the fields of data storage and information security due to its remarkable properties of high throughput, flexible design, low cost, and facile operation.…”
mentioning
confidence: 99%